PROSPEK PENGEMBANGAN PUSAT-PUSAT PEMBIBITAN SAPI BALI DI LAHAN MARGINAL UNTUK MENDUKUNG PENYEDIAAN SAPI BAKALAN DI NUSA TENGGARA BARAT - Mashur Mashur (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2014)
Cattle are an important component in a farming system in West Nusa Tenggara. Farmers' lives can hardly be separated from livestock, although the basic needs of the farm family are met from food crops. Cow dwelling system, especially in Lombok Island using cages gathering (collective cage), so the security of cattle more secure and coaching more easily implemented. The demand for cattle from West Nusa Tenggara continues to increase as the Bali cattle from West Nusa Tenggara are free from disease (Mouth, Nails, Brucellosis, and SE). Adaptability is quite good and high fertility and purity is more assured. The increasing rate of demand is expected to have exceeded the production capability, which tends to decrease the population of cattle. If the development of Bali cattle with integrated management based on collective cages applied to all areas in West Nusa Tenggara is expected to grow Bali cattle breeding centers in rural areas with superior production, uniform and continuous so as to support the provision of seed and beef cattle in West Nusa Tenggara . To find out the prospect of development of Bali Cow breeding centers on marginal land to support the supply of beef cattle in West Nusa Tenggara has been done by survey method from January to December 2012 in 10 regencies / cities as West Nusa Tenggara.